2012
DOI: 10.1063/1.4703924
|View full text |Cite
|
Sign up to set email alerts
|

Landau-Levich flow visualization: Revealing the flow topology responsible for the film thickening phenomena

Abstract: An extensive body of experimental work has proven the validity of the analysis of Landau and Levich, who were the first to determine theoretically the thickness of the film deposited by the withdrawal of a flat substrate from a bath of liquid with a clean interface. However, there are a number of experimental investigations that have shown that surfactants in the liquid may result in a thickening of the deposited film. Marangoni phenomena have usually been considered responsible for this effect. However, some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 80 publications
2
48
0
1
Order By: Relevance
“…Much less is known concerning the flow inside the bath. At least it was shown that different flow regimes can be observed, but the liquid flows at any point inside the bath [4], so that the transition from the bath to the surface is smooth.…”
Section: Introductionmentioning
confidence: 98%
“…Much less is known concerning the flow inside the bath. At least it was shown that different flow regimes can be observed, but the liquid flows at any point inside the bath [4], so that the transition from the bath to the surface is smooth.…”
Section: Introductionmentioning
confidence: 98%
“…First, considering a constant electric field (even in the dynamic meniscus) should be examined in more detail. The stick boundary condition for the velocity at the interface should also be scrutinized and explored with other types of surfactants; indeed, the variations of the numerical prefactor in the Frankel's law versus surfactant type are still a subject of active debate [17][18][19]. Eventually, polarization effects near the surfaces result in deviations from continuous description, suggesting that Poisson-Boltzmann theory is questionable in these films [20].…”
mentioning
confidence: 99%
“…This equation was established assuming that the thickness of fluid layer is homogeneous due to a delicate balance between the viscous drag and the wetting property (adhesion) of the fluid with the substrate surface [31,32]. Therefore, the thickness of the PAN films in our experiments was controlled by adjusting the solution Table 2).…”
Section: Pan Films Deposited By Dip-coatingmentioning
confidence: 99%